GERENCIAMENTO DE LEGITIMAÇÃO SOCIAL: O USO DO DISCURSO NO RELATO INTEGRADO APÓS CRISE - Adams, Caroline (2022)
The objective of this paper is to analyze the discourse of the Integrated Report, after the crisis. Checking the company's positioning in its Integrated Reports after having problems with social legitimacy. Using Legitimacy Theory as the base theory and Suchman's (1995) model for discourse analysis. Methodology used: Discourse analysis based on the Suchman model (1995). The Renner Group used in its speech a position of moral and cognitive gain and maintenance during the studied period. Seeking to institutionalize its processes and demonstrate that it does what is expected, according to the expectations of the society around it. Another relevant point identified was the non-use of a pragmatic recovery point, this position has as its main characteristic of discrimination and denial of the problem. The company took responsibility and worked to resolve the issue.